2020
DOI: 10.1111/acem.14000
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Controlled Trial of the PTSD Coach App Following Motor Vehicle Crash–related Injury

Abstract: Objective: Posttraumatic stress disorder (PTSD) symptoms (PTSS) are common after minor injuries and can impair recovery. We sought to understand whether an evidence-based mobile phone application with self-help tools (PTSD Coach) could be useful to improve recovery after acute trauma among injured emergency department (ED) patients. This pilot study examined the feasibility, acceptability, and potential benefit of using PTSD Coach among acutely injured motor vehicle crash (MVC) patients. Methods: From Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…Forty-six subjects (73%) were retained at 90 days; retention analyses revealed no differences in demographic factors or ED psychological variables between those retained versus not retained at 90 days. We previously reported that no group differences were present for subjects in the PTSD Coach and TAU groups regarding baseline demographic characteristics or key study variables (Pacella-LaBarbara et al, 2020).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Forty-six subjects (73%) were retained at 90 days; retention analyses revealed no differences in demographic factors or ED psychological variables between those retained versus not retained at 90 days. We previously reported that no group differences were present for subjects in the PTSD Coach and TAU groups regarding baseline demographic characteristics or key study variables (Pacella-LaBarbara et al, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…This study was based on secondary data analysis of a randomized clinical trial (ClinicalTrials.gov Identifier: NCT03247179) testing the use of a smartphone app (“PTSD Coach”) to prevent postinjury PTSS (Pacella-LaBarbara et al, 2020). No overall group differences emerged for outcomes at 90 days postinjury; as such, we collapsed treatment groups for analysis in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted April 26, 2021. ; https://doi.org/10.1101/2021.04.23.21256003 doi: medRxiv preprint the app, which could affect their user experience and outcome in more negative ways. As seen in previous studies with the PTSD Coach app, some participants may experience difficulties with downloading or installing the app, or to remember to use it more than once during an ongoing intervention (64,65). In the My Grief app, a daily reminder can be set up to remind them to rate their grief in the grief chart self-assessment.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in previous studies with the PTSD Coach app, some participants may experience difficulties with downloading or installing the app, or to remember to use it more than once during an ongoing intervention. 64 65 In the My Grief app, a daily reminder can be set up to remind them to rate their grief in the grief chart self-assessment. The research group will also make a phone call to each user, about 1 week from registration, to check if everything is working.…”
Section: Discussionmentioning
confidence: 99%